Ter em mente (meinen) e forma de vida (lebensform): elementos estruturantes da negação do ato mental no segundo Wittgenstein. - Silva Filho, José Maria da (2022)
The objective of this work is to present the role played by the verb meinen (to mean) and its apparent connection with mental processes, in the work published posthumously by Wittgenstein, the Philosophical Investigations. For this, we go through the same work in an attempt to bring to view the conclusions presented by the Austrian philosopher. What is intended, moreover, is, corroborating these same conclusions, to present and explain that, in its last instance (of keeping in mind), the concept is much less explicit, due to its very few appearances, in the same work, called lebensform (form of life). Such a concept, we believe, plays a fundamental role in Wittgenstein's thought in its last phase. Therefore, we will turn our attention in order to, later on, show that it appears to us as a last resort, including in the denial of the meinen as a denial of mental processes. For this, we will use both the author's bibliography and that of commentators and experts on Wittgenstein, always with the help of our advisor, in fulfilling such a request.